THE MEANING OF MINDFULNESS IN SONG LYRICS OF “SORAI” BY NADIN AMIZAH - Azka Adhani Putri; Muhammad Farhan Fuadi; Muhammad Faisal Mufhadhal (Jurnal Pustaka Komunikasi, 2023)
Public Relation Practitioner’s role is to provide a good message to the target audience. As a musician, Nadin Amizah’s way to communicate with her audience is through her song and lyrics. Song lyrics are an important element in a song that contains a story or message for the listener. This research aims to find the meaning behind the song “Sorai” by Nadin Amizah and to further discuss mindfulness elements in the song through qualitative method and semiotic theory by Ferdinand de Saussure. This research is to be analyzed using five elements of mindfulness based on Aldina’s theory of mindfulness. The result of the analysis of Sorai by Nadin Amizah consists of a meaningful and heartfelt attitude towards accepting and letting go of a separation through mindfulness. Through mindfulness, letting go and accepting what is happening in our lives becomes easier. It proves how mindfulness is a necessary element to be applied in our day to day life in order to have a peaceful and meaningful life.